ENERGY EFFICIENCY AS AN ESSENTIAL COMPONENT OF COMPETENCE OF FUTURE SKILLED WORKERS HAVING MACHINE-BUILDING PROFILE - Hlushchenko, Olena (Professional Pedagogics, 2015)
The article identifies factors that determine importance of skilled workers training, who are competent on the issues of efficient use of energy resources. Attention is drawn to the fact that the problems of energy efficiency are considered at the international and national levels in legal documents, projects, strategic programs of development hence emphasizing their importance and relevance. The author explains the work of the All-Ukrainian Centre "Energy efficiency in vocational education and industry" of the Institute of vocational education and training of the National Academy of Pedagogical Sciences of Ukraine on questions of vocational training of future specialists and increase of teachers’ level of readiness to use knowledge concerning efficiency foundations in their professional activity. The author formulates a definition as to energy efficient competence of metalworker-electricians on electrical equipment repair. This competence involves the awareness, understanding and comprehension of the importance of rational energy consumption; the feasibility of theoretical knowledge acquisition concerning efficient use of electricity, practical skills, values, and competences; the availability of appropriate personal qualities. The use of a workbook with tasks, tests, technical dictations, and exercises regarding the efficient use of electricity in vocational training of skilled workers is considered to be one of the options to solve problems concerning the filling of majors’ content and on-the-job training with energy efficiency materials. A description of the above mentioned workbook, which was developed according to the content of a Standard curriculum on the subject "Electrical engineering basics of industrial electronics", is given. The author describes its structure and content and concludes that it is reasonable to consider the formation of the energy efficiency competence of skilled workers employed in a machine-building industry as a continuous process.
Keywords: energy efficient competence; efficient use of energy resources